Depression Among University Students During Covid-19 Pandemic: An Online-Based Cross-Sectional Study - Ranti Ekasari; Ahmad (Saintika Medika, 2022)
COVID-19 is a new communicable disease that spread all over the world and becomes a pandemic. It also caused psychological conditions like depression. Students were one of the groups who have a high opportunity to get depressed. Since students are in a transitional period of early adulthood, they are facing another form of adjustment that can trigger depression.This study aimed to know the depression level of students at Universitas Islam NegeriAlauddin Makassar and some factors that were thought to have a relation to the depression level.This is quantitative research, in which a cross-sectional study design used primary data taken from August 1 until August 12, 2021, via a Google Form. The total sample was 344 respondents.Most of the respondents tend to have normal levels of depression. Age, gender, period of learning, and learning challenges were being the variable that had a significant correlation with depression level. Whilst, faculty and learning media had not.In order to tackle down the depression of students, it is necessary to have the cooperation of various parties, including from the campus, the family, and the role of students in managing information.